ChemInform Abstract: MaxPHOS Ligand: PH/NH Tautomerism and Rhodium‐Catalyzed Asymmetric Hydrogenations. Issue 35 (2nd September 2014) - Cristobal‐Lecina, Edgar; Etayo, Pablo; Doran, Sean; Reves, Marc; Martin‐Gago, Pablo; Grabulosa, Arnald; Costantino, Andrea R.; Vidal‐Ferran, Anton; Riera, Antoni; Verdaguer, Xavier
Abstract The rhodium complex containing the (S)‐MaxPhos ligand is synthesized and examined as catalyst for the asymmetric hydrogenation reaction of a variety of di‐ and trisubstituted olefins.